Information sharing in community policing in Europe: Building public confidence - Aston, Elizabeth (European journal of criminology, 2023)
The literature on the importance of procedural justice in policing is extensive. Using the context of information sharing in community policing, this paper argues that interactional, procedural and distributive justice are salient in interactions between the police and the public, both online and face-to-face. Structured interviews (n?=?161) were conducted with members of young minority groups and intermediaries (who work with minorities and police agencies) across nine countries in Europe. Our analysis of barriers and facilitators to sharing information with the police highlights processes of interactional, procedural and distributive justice in building public confidence. We highlight theoretical and practical implications of relevance to policing internationally. Our findings show that demonstrating aspects of interactional justice (attitude and behaviour, accessibility and communication, personal contact and relationships); procedural justice (responsiveness and efficiency, data protection and security); and distributive justice (outcomes and effectiveness, equity in distribution of policing services) have a role in building public confidence and facilitating information sharing with police online and face-to-face. We conclude that in addition to micro-level interactions, meso-level social processes (e.g. community policing models and data protection and security procedures) can be useful in enhancing public confidence.